Gender in Agency-Structure Debate - Bhusal, Durga (Journal of Advanced Research in Humanities and Social Sciences; Vol 7 No 3 (2020): Journal of Advanced Research in Humanities and Social Science, 2021)
This study sheds light on conceptual debates on domination of agency and structure in socioeconomic stratification. Various angles of thoughts—Marxists, Functionalists, Feminists, New right, and New labor—on defining family and gender role are guiding tools to understand the association between gender and agency-structure. Various perspectives of school of thoughts are taken into account to clarify the debate in order to fulfil the purpose of this article. Criticism on structural approach and agency structure debate manifest the presence of different lines of thought- structural approach as passive objects, household as the most relevant unit of utility maximization, cooperative conflict is important in intra-family decisions, on defining agency and structure. Members of the family, division of labor, decision making roles are influenced by structure; and neither gender nor the structure lonely sufficient to explain the decisions taking in family, is crux of this study. This article concludes by deliberating guiding principle for further study. How to cite this article:  Bhusal D. Gender in Agency-Structure Debate. J Adv Res Humani Social Sci 2020; 7(3): 13-17.